2019 IEEE 17th International Conference on Industrial Informatics (INDIN) 2019
DOI: 10.1109/indin41052.2019.8972280
|View full text |Cite
|
Sign up to set email alerts
|

IoT Demonstration Platform for Education and Research

Abstract: Internet of things (IoT) and digitalization of industries are changing the skills required from newly graduated engineers. To truly master these skills, they must be included in the curriculum, and a platform on which students can create IoT projects is needed. The research of IoT and related areas also benefits from such a platform. The platform presented in this paper focuses on a simple coffee maker but applies techniques and tools which are also used in larger scale projects, thereby making the system a va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…Waheed et al [25] documented that IoT facilitates organizations in building digital platforms and adopting machine learning. The prior findings of Nykyri et al [34] suggested that IoT is a set of all processes and applications of technological resources to develop platforms for acquisition and dissemination of data and information.…”
Section: Discussionmentioning
confidence: 99%
“…Waheed et al [25] documented that IoT facilitates organizations in building digital platforms and adopting machine learning. The prior findings of Nykyri et al [34] suggested that IoT is a set of all processes and applications of technological resources to develop platforms for acquisition and dissemination of data and information.…”
Section: Discussionmentioning
confidence: 99%
“…As observed in Fig. 9, home automation projects form the most widely reported real-world applications in IoT-based curricula [33], [36], [37], [41], [42], [44], [45], [78], [80], [91], [143]. Home automation projects apply to every aspect of daily life and are colloquially characterized as Smart applications.…”
Section: B Home Automationmentioning
confidence: 99%
“…In [45], and [36], students designed a coffee pot that communicated detailed information on the amount of coffee consumption and brewing time with a user. The authors of [36] reported on graduate Electrical Engineering (EE) and MBA students developing Cafe IoT -an IoT system that acquired and displayed data from a coffee maker in the break [31], [32], [34], [38], [42], [45], [78], [109] Home Automation Smart Coffee Machines, Integrated Smart House, Smart Home Security, Smart Faucet, Smart Refrigerator, Smart Pet Access Control System, Smart Morning Mat, Smart Water Bottle, Fire and Shock Detection, Smart Water Leak System [36], [37], [41], [44], [45], [78], [80], [91], [143], [144] Connected Infrastructure Smart Parking System, Smart Transportation -Wheelchairs, Bus Stop, and Bus Networks, Smart waste collection system [37], [41], [78], [127], Connected Biomedical Devices Baby Monitoring, Smart Wearable [37], [45]- [47], [143] Educational Robots Bluetooth and Wifi Controlled robots [52], [126] FIGURE 9: Student projects covering real-world applications noted in the literature reviewed in this paper room of the university. The system tracked the break room usage using Infrared motion sensors, the power consumption of the coffee maker, and the amount of brewed coffee.…”
Section: ) Smart Coffee Machinesmentioning
confidence: 99%
“…The IBM Cloud was used to host development tools and technologies for implementing the IoT devices. IBM Watson IoT Platform [ 66 ] was chosen to host IoT devices and gateways. The Node-Red server provided communication between the IoT devices and servers while using the Constrained Application Protocol (CoAP).…”
Section: Framework Implementationmentioning
confidence: 99%